Key Drivers of Organizational Commitment Worldwide through Motivation and Environment: Pendorong Utama Komitmen Organisasi di Seluruh Dunia melalui Motivasi dan Lingkungan - Azizi , Achmad; Firdaus, Vera (Indonesian Journal of Innovation Studies, 2024)
This study explores the influence of work motivation, individual characteristics, and the work environment on organizational commitment at CV. Juke Abadi Sidoarjo, employing quantitative research with 60 respondents. Utilizing regression analysis through SmartPLS software, findings reveal significant positive relationships between work motivation, individual characteristics, the work environment, and organizational commitment. These results underscore the importance of fostering work motivation, cultivating desirable individual traits, and maintaining conducive work environments to bolster organizational commitment. By understanding and addressing these factors, organizations can enhance employee engagement and ultimately achieve organizational success. Highlights: 1. Quantitative research: Utilized regression analysis and SmartPLS software.2. Positive findings: Significant relationships between work motivation and organizational commitment.3. Practical implications: Importance of fostering motivation and conducive work environments. Keywords: Organizational commitment, Work motivation, Individual characteristics, Work environment, CV. Juke Abadi Sidoarjo